2020
DOI: 10.1021/acsphotonics.9b01540
|View full text |Cite
|
Sign up to set email alerts
|

Inverse-Designed Photonics for Semiconductor Foundries

Abstract: Silicon photonics is becoming a leading technology in photonics, displacing traditional fiber optic transceivers and enabling new applications. Further improving the density and performance of silicon photonics, however, has been challenging, due to the large size and limited performance of traditional semi-analytically designed components. Automated optimization of photonic devices using inverse design is a promising path forward but has until now faced difficulties in producing designs that can be fabricated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 29 publications
(67 reference statements)
0
48
0
Order By: Relevance
“…The designed structures are difficult to fabricate at the nanoscale for optical applications, but the design process is flexible enough to incorporate nanoscale fabrication requirements as shown in other works [30]. In particular, some areas of fabrication that can fabricate the required subwavelength features for these devices include: multilayer fabrication common in CMOS or MEMS processes [31]; direct-write two-photon laser lithography capable of designing subwavelength 3D elements in the infrared [17]; and closely aligned stacks of Silicon wafers with subwavelength features at terahertz frequencies [32]. All of these techniques have demonstrated active mechanical control that could be useful for multiplexing functions like what was demonstrated in this work.…”
Section: Discussionmentioning
confidence: 99%
“…The designed structures are difficult to fabricate at the nanoscale for optical applications, but the design process is flexible enough to incorporate nanoscale fabrication requirements as shown in other works [30]. In particular, some areas of fabrication that can fabricate the required subwavelength features for these devices include: multilayer fabrication common in CMOS or MEMS processes [31]; direct-write two-photon laser lithography capable of designing subwavelength 3D elements in the infrared [17]; and closely aligned stacks of Silicon wafers with subwavelength features at terahertz frequencies [32]. All of these techniques have demonstrated active mechanical control that could be useful for multiplexing functions like what was demonstrated in this work.…”
Section: Discussionmentioning
confidence: 99%
“…[ 256 ] Remarkably, the system architecture has been optimized by so‐called inverse design, as currently used for designing complex electrodynamic systems. [ 257 ] It has been demonstrated that χ (3) nonlinear resonators can be used to achieve fully passive, bias‐free nonreciprocal pulse routing in standard silicon photonic platforms. To overcome the constraints of Equation (), this system consists of cascaded nonlinear Fano and Lorentzian resonators.…”
Section: Nonreciprocity Based On Nonlinearitymentioning
confidence: 99%
“…Mode converters are a prototypical 47 example for integrated photonic devices commonly found in on-chip integrated optical systems. 48,49 The ability to design such functionalities for free-form geometries could potentially lead to integration of these designs into e.g. photonic wire bonds.…”
Section: Mode Convertermentioning
confidence: 99%